Knowledge-based cost modelling for innovative design - Rehman, S. (Cranfield University, 2000)
The contribution to new knowledge from this research is a novel method for modelling production costs throughout the design phase of a product's lifecycle, from conceptual to detail design. The provision of cost data throughout the design phase allows management to make more accurate bid estimates and encourages designers to design to cost, leading to a reduction in the amount of design rework and product's time to market. The cost modelling strategy adopted incorporates the use of knowledge-based and case-based approaches. Cost estimation is automated by linking design knowledge, required for predicting design features from incomplete design descriptions, to production knowledge. The link between the different paradigms is achieved through the blackboard framework of problem solving which incorporates both case-baseda nd rule-based reasoning. The method described is aimed at innovative design activities in which original designs are produced which are similar to some extent to past design solutions. The method is validated through a prototyping approach. Tests conducted on the prototype confirm that the designed method models costs sufficiently accurately within the range of its own knowledge base. It can therefore be inferred that the designed cost modelling methodology sets out a feasible approach to cost estimation throughout the design phase.